w-9*w-3*w

The powers are -9 and -3 , but positive exponents only .

Hello!

I rewrite this using ^ as a symbol of rising to power. Also I use enough parenthesis:

w^(-9)*w^(-3)*w.

Consider that w = w^1 and use the corresponding law:

w^(-9)*w^(-3)*w = w^(-9)*w^(-3)*w^1 = w^(-9-3+1) = w^(-11).

The exponent is negative. We can make it positive sending w^11 to the denominator:

w^(-11) = 1/(w^11).

Another option is to change the base to 1/w:

w^(-11) = [w^(-1)]^11 = (1/w)^11. Use more suitable option.

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up